Socialization of Good Communication for MSMEs to Increase Revenue and Service Quality: Pengabdian - Nova Ch. Mamuaya; Rizal Bakti; Muh. Taufik Iqbal; Eris Nur Dirman; Olivia Tahalele (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
A fundamental problem hindering the acceleration of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia is the low level of service communication competency, which results in poor customer experience and low sales conversion rates. This community service activity aims to socialize and provide assistance in effective communication strategies to improve service quality and partner operational income. This program is implemented collaboratively by a consortium of academics from four strategic institutions: Manado State University, Jakarta Global University, Fajar University, and Pattimura University. The implementation method uses Participatory Technology Assistance (PTA) which includes persuasive communication workshops, service excellence training, and the implementation of an AI-based communication assistant (ChatGPT) for digital service optimization. The results of the activity show an 88% increase in partner understanding of business communication ethics and a positive correlation with a 15-20% increase in daily turnover in the first month after the intervention. This synergy has succeeded in creating service communication standards that are adaptive to local cultural characteristics in North Sulawesi, Jakarta, Makassar, and Maluku.